Penggunaan Software 3D Slicer pada Pemodelan dan Visualisasi Volumetrik Meningioma - Marufah, Asmaul Lutfi; Annas, Muhamad Azwar (TSAQOFAH, 2023)
Meningioma is a tumor that is often found in Indonesia. Treatment for meningomenia itself can be through surgery, radiotherapy, or a combination of both. The decision to carry out radiotherapy itself must go through a planning stage using a treatment planning system (TPS) which requires accurate 3D volumetric imaging. On the other hand, 3D slicer itself is 3D imaging software that is commonly used in the field of radiology. Therefore, this study aims to find out how to use 3D slicer software in modeling and volumetric visualization of meningioma disease. This study uses MRI data from meningioma patients which are processed for volumetric segmentation with a 3D slicer. Based on the results obtained, it can be concluded that the 3D slicer software is effective for modeling and visualizing volumetric brain tumor disease. In this case the visualization & volumetrics look clear and relatively accurate, namely a volume of 16,8402 cm3 with an accuracy of 98.5%.